Analisis Nilai Kearifan lokal Kampung Naga Berbasis Pelestarian Lingkungan Sebagai Upaya Masyarakat Dalam Mengelola Lingkungan - Mulyanie, Erni; Hilman Hakim, Erwin; Indrianeu, Tineu; Al Husaini, Hamzah; Rismawati, Resi (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2023)
The life of Kampung Naga is a clear example of efforts to manage the environment through local wisdom which is still maintained, especially in inner Kampung Naga, so that the environment around us can provide many positive benefits to other living things. The purpose of this study was to examine local wisdom values based on environmental preservation in Kampung Naga as a community effort to keep their environmental beautiful. The research methode used is a qualitative descriptive approach. The data analysis used comes from observations, literature studies, and documentation. The Results of this study are that the people of Kampung Naga make efforts to preserve the environment by applying local wisdom based the environment, including forbidden forests, regional zoning, pamali, stilt house, and swales. The conclusion of this study is that local wisdom values based on environmental preservation are the way people protect their environment so that they can provide positive benefits for other living things.